2005
DOI: 10.18388/abp.2005_3436
|View full text |Cite
|
Sign up to set email alerts
|

High pressure processing for food safety.

Abstract: Food preservation using high pressure is a promising technique in food industry as it offers numerous opportunities for developing new foods with extended shelf-life, high nutritional value and excellent organoleptic characteristics. High pressure is an alternative to thermal processing. The resistance of microorganisms to pressure varies considerably depending on the pressure range applied, temperature and treatment duration, and type of microorganism. Generally, Gram-positive bacteria are more resistant to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 5 publications
(4 reference statements)
1
16
0
12
Order By: Relevance
“…Ding and others (2001) observed that higher pressure conditions (345 and 550 MPa) and longer exposure times (10 and 30 min) achieved a greater reduction in numbers of undesirable bacteria in the natural microflora of Swiss cheese slurries (coliforms, presumptive coagulase‐positive Staphylococcus , yeasts, and molds) and in starter LAB added to milk for acid production and flavor development. Fonberg‐Broczek and others (2005) found that A. hydrophila strains (Państwowy Instytut Weterynaryjny N.98, Państwowy Inspekcja Sanitarna N. 98, Inspekcja Sanitarna N. 95) in samples of Gouda cheese treated at 100 MPa and 50 °C had a D‐value of 32.05 min, while at 200 MPa the D‐value fell to 12.97 min, and to 2.43 min when subjected to 300 MPa. More recently, in raw milk Cheddar cheese, an increase in pressure intensity from 250 to 350 MPa applied at 25 °C resulted in a decrease of D‐values from 23.5 to 1.4 min for L. monocytogenes Scott A (Shao and others 2007).…”
Section: Effect Of High Hydrostatic Pressure On Vegetative Forms Of Mmentioning
confidence: 97%
“…Ding and others (2001) observed that higher pressure conditions (345 and 550 MPa) and longer exposure times (10 and 30 min) achieved a greater reduction in numbers of undesirable bacteria in the natural microflora of Swiss cheese slurries (coliforms, presumptive coagulase‐positive Staphylococcus , yeasts, and molds) and in starter LAB added to milk for acid production and flavor development. Fonberg‐Broczek and others (2005) found that A. hydrophila strains (Państwowy Instytut Weterynaryjny N.98, Państwowy Inspekcja Sanitarna N. 98, Inspekcja Sanitarna N. 95) in samples of Gouda cheese treated at 100 MPa and 50 °C had a D‐value of 32.05 min, while at 200 MPa the D‐value fell to 12.97 min, and to 2.43 min when subjected to 300 MPa. More recently, in raw milk Cheddar cheese, an increase in pressure intensity from 250 to 350 MPa applied at 25 °C resulted in a decrease of D‐values from 23.5 to 1.4 min for L. monocytogenes Scott A (Shao and others 2007).…”
Section: Effect Of High Hydrostatic Pressure On Vegetative Forms Of Mmentioning
confidence: 97%
“…Formy wegetatywne drobnoustrojów są bardziej wrażliwe na działanie wysokiego ciśnienia, natomiast przetrwalniki można zniszczyć tylko w fazie kiełkowania lub stosując bardzo wysokie ciśnienie (powyżej 800 MPa) i ewentualnie podwyższoną temperaturę, co jest opisywane w piśmiennictwie. Szczególnie podkreślana jest skuteczność stosowania HPP jako procesu zapewniającego eliminację z mięsa i jego produktów bakterii z rodzaju: Salmonella, Campylobacter jejuni, Listeria monocytogenes, a także Aeromonas hydrophila [1,2,4,11,28].…”
unclassified
“…However, it has certain limitations because it is only possible to use it in batch and/or semi-continuous processes (Hayashi, 1989;Vachon et al, 2002). Fonberg-Broczek et al (2005) reviewed the high-pressure processing for food safety. High pressure is a viable alternative to thermal processing.…”
Section: New Industrial Sterilization Technologiesmentioning
confidence: 99%